The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1182/blood-2010-08-301531
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1–related Hodgkin lymphoma in the era of combination antiretroviral therapy: incidence and evolution of CD4+ T-cell lymphocytes

Abstract: The risk of Hodgkin lymphoma (HL) is in-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 45 publications
6
75
1
2
Order By: Relevance
“…4 This observation was possible because CD4 þ T-cell blood counts in HIV-patients are usually well documented. It can be expected that HIV-negative individuals will react in the same manner, although this has not been documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 This observation was possible because CD4 þ T-cell blood counts in HIV-patients are usually well documented. It can be expected that HIV-negative individuals will react in the same manner, although this has not been documented.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Although HIV-related classical Hodgkin lymphoma occurs at any CD4 blood count, it is most frequently observed in patients with a moderate immune deficiency and CD4 blood counts of 150-249 cells/ml. 2,4 As Hodgkin-and Reed-Sternberg cells, the tumor cells in classical Hodgkin lymphoma, usually constitute a small subpopulation of the cells in affected lymph nodes; it is likely that the microenvironment, largely composed of CD4 þ T regulatory 1 cells, has an essential role in the pathophysiology of the disease. 5 As HIV infection usually involves decreased CD4 þ T-cell counts in the peripheral blood, several studies have addressed the issue of the microenvironment in HIV-associated Hodgkin lymphoma and have found the CD4/CD8 T-cell ratio to be inverted.…”
mentioning
confidence: 99%
“…1 A recent analysis of combined European cohorts of HIV-infected individuals has revealed that combination antiretroviral therapy (cART) reduces the incidence of HL. 2 The optimal treatment for patients with immunocompetent HL continues to evolve. In randomized, controlled studies that include immunocompetent patients with classical HL, it has been demonstrated that the combination of doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) is effective and is probably less toxic than more intensive regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Patients whose CD4 cell counts declined despite suppression of HIV-1 replication on cART were at increased risk of Hodgkin's lymphoma. 29 Comparative analyses are planned in collaboration with the African regions of IeDEA. 4 …”
Section: Opportunistic Infectionsmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 The COHERE malignancy group has focused on defining the incidence, risk factors and prognosis of HIV-associated cancers in the cART era, with a focus on systemic non-Hodgkin lymphoma (NHL) and primary brain lymphoma (PBL), Hodgkin's lymphoma and, more recently, Kaposi's sarcoma. [28][29][30] The incidence of non-Hodgkin's lymphoma, primary brain lymphoma and Kaposi's sarcoma were substantially reduced in patients on cART, and timely initiation of therapy at high CD4 cell counts is important for preventing these malignancies. 28,30 In contrast, the incidence of Hodgkin's lymphoma was not reduced by cART.…”
Section: Opportunistic Infectionsmentioning
confidence: 99%